Evolution of a protein folding nucleus. (10th December 2015) - Xia, Xue; Longo, Liam M.; Sutherland, Mason A.; Blaber, Michael
Abstract: The folding nucleus (FN) is a cryptic element within protein primary structure that enables an efficient folding pathway and is the postulated heritable element in the evolution of protein architecture; however, almost nothing is known regarding how the FN structurally changes as complex protein architecture evolves from simpler peptide motifs. We report characterization of the FN of a designed purely symmetric β‐trefoil protein by ϕ ‐value analysis. We compare the structure and folding properties of key foldable intermediates along the evolutionary trajectory of the β‐trefoil. The results show structural acquisition of the FN during gene fusion events, incorporating novel turn structure created by gene fusion. Furthermore, the FN is adjusted by circular permutation in response to destabilizing functional mutation. FN plasticity by way of circular permutation is made possible by the intrinsic C 3 cyclic symmetry of the β‐trefoil architecture, identifying a possible selective advantage that helps explain the prevalence of cyclic structural symmetry in the proteome.